CO[2] Sequestration by Natural Zeolite for Greenhouse Effect Control - Hernandez M. A. Miguel Angel; Pestryakov A. N. Aleksey Nikolaevich; Portillo R. Roberto; Salgado M. A. Martha; Rojas F. Fernando; Rubio E. Efrain; Ruiz S. Sinuhe; Petranovskii V. Vitalii (2015, 2015)
Title screen